Analisis Strategi Marketing Mix dalam Upaya Meningkatkan Minat Beli Konsumen di Manov Kopi Mojokerto - Putry Meysa Selvina; R. Yuniardi Rusdianto (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the implementation of the marketing mix strategy in increasing consumer purchase intention at Manov Kopi Mojokerto. A descriptive qualitative approach was employed, with data collected through observation, in-depth interviews, and documentation. The results indicate that the 7P marketing mix plays a significant role in enhancing consumer attraction and purchase intention. SWOT analysis reveals strength and weakness scores of 2.87 and 0.42, while opportunity and threat scores are 3.02 and 0.30, respectively. The IFAS and EFAS matrices yield scores of 3.29 and 3.32, indicating strong internal conditions and favorable external opportunities. The SWOT matrix positions Manov Kopi in Quadrant I (grow and build), suggesting an aggressive growth strategy. The recommended strategy is Strength–Opportunities (SO), which emphasizes leveraging internal strengths to optimize external opportunities in increasing consumer purchase intention.